Marketing Factors and Consumer’s Value Perception Affecting the Fear of Missing Out (FOMO) on the Behavior of Using Café Bakery Services - Upama, Rapeepong; Lomprakhon, Chirawut; Sae-eiaw, Kanda (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2024)
The objective of this research is to study the factors and behaviours related to the actual usage of bakery cafe services by the FOMO group. The research includes the 7Ps of Marketing, social perception factors, and emotional perception factors. It employed a quantitative research approach, specifically survey research, using a questionnaire administered to a sample of 400 customers of bakery cafes in Bangkok. The study applied statistical methodologies such as percentages, means, standard deviations,and Factor Analysis which includes Principal Component Analysis (PCA), and Varimax method to analyse the data. The research findings indicate the rank of important factors in the 7Ps of marketing for the FOMO group: 1) In-store service - cheerful and friendly employees who are genuine 2) Store-produced video clips providing product knowledge 3) Store located in a modern and trendy commercial center 4) Store offering freebies or giveaways and 5) Products being priced lower than other The most influential factors in the perception of social value for the FOMO (Fear of Missing Out) group are being praised and celebrated in the online community for consuming products and services at coffee bakery shops. Additionally, the most significant factor in the emotional value perception for the FOMO group is feeling the utmost pleasure when consuming products and services at coffee bakery shops. These research findings can be used as guidance for developing products and services to meet the needs of the FOMO group, as well as for creating marketing strategies to keep up with the current era.